2015
DOI: 10.1016/j.jelectrocard.2014.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone ECG for evaluation of STEMI: Results of the ST LEUIS Pilot Study

Abstract: Background: 12-lead ECG is a critical component of initial evaluation of cardiac ischemia, but has traditionally been limited to large, dedicated equipment in medical care environments. Smartphones provide a potential alternative platform for the extension of ECG to new care settings and to improve timeliness of care. Objective: To gain experience with smartphone electrocardiography prior to designing a larger multicenter study evaluating standard 12-lead ECG compared to smartphone ECG. Methods: 6 patients for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(44 citation statements)
references
References 7 publications
2
38
0
4
Order By: Relevance
“…Smartphone-based electrocardiography is a promising, developing technology intended to increase availability and speed of electrocardiographic evaluation [2] .This case confirms the potential of a smartphone ECG for evaluation of the P waves and arrhythmias in comparison with a standard record. This device has an excellent correlation with the gold standard 12-lead ECG.…”
Section: Discussionsupporting
confidence: 66%
“…Smartphone-based electrocardiography is a promising, developing technology intended to increase availability and speed of electrocardiographic evaluation [2] .This case confirms the potential of a smartphone ECG for evaluation of the P waves and arrhythmias in comparison with a standard record. This device has an excellent correlation with the gold standard 12-lead ECG.…”
Section: Discussionsupporting
confidence: 66%
“…The device has also been shown to be used to successfully monitor college athletes experiencing heart palpitations for potentially adverse arrhythmias in real-time [15]. Future implications have been made for the evaluation of acute ischemia with the device in people [16]. There appear to be many future applications for this device in water buffaloes.…”
Section: Discussionmentioning
confidence: 99%
“…There was agreement in all 6 patients (4 with ST-segment-elevation myocardial infarction and 2 with non-ST-segment-elevation myocardial infarction). 90 One study from St. Louis, Missouri reported that this technology can generate tracings of diagnostic quality in children with positive user satisfaction and could be used to manage children with supraventricular tachycardia and atrial fibrillation. 72 …”
Section: Personal Tele-electrophysiologymentioning
confidence: 99%
“…128 Most of these applications rely solely on video and audio connections with additional software for scheduling, billing, sharing of still-frame images, and documentation. However, some peripherals such as a smartphone-compatible heart rhythm detection devices 90 and otoscopes 129 may be available for purchase for a low price. One could imagine that this technology could be used to manage children and adults in follow-up of syncope, chest pain, obesity, hypercholesterolemia, and chronic heart failure.…”
Section: Direct-to-consumer Telemedicinementioning
confidence: 99%